The impact of road salting on the roadside soil condition with different levels of maintenance - Stankevičiūtė, Goda; Ignatavičius, Gytautas; Valskys, Vaidotas (International Conference “Environmental Engineering”, 2026)
Salts used to reduce road icing alter the chemical composition of soil and induce ion imbalance, potentially leading to geochemical anomalies in roadside soils. This environmental problem is relevant in Lithuania due to the large amounts of technical salt spread on roads annually. This study investigates the relationship between road maintenance intensity (K3, K4, K5, and K5ž) and heavy metal concentrations in roadside soils. The research was conducted in the Biržai district, selecting nearby roads to ensure relative homogeneity of natural conditions and reduce potential distortions from external factors. The results show that higher concentrations of certain heavy metals are associated with more intensively maintained roads compared to background levels. These findings suggest that intensive use of road de-icing salts can significantly affect roadside soil quality and highlight the need for more environmentally friendly maintenance practices.
Keywords: heavy metals; road salting; roadside soil; maintenance levels